Sweden : Financial Sector Assessment Program Update: Technical Note on Contingent Claims Analysis Approach to Measure Risk and Stress Test the Swedish Banking Sector. (IMF Staff Country Reports; Country Report ;, 2011)
This paper describes the application of contingent claims analysis (CCA) and systemic CCA to the top four commercial banks in Sweden. The balance sheet stress tests for four major banks were complemented with tests based on the CCA framework, a risk-adjusted balance sheet relating bank asset values to equity value, default risk, and bank funding costs. Even though the results show that banks are found to be resilient to shocks, more work on systemic risk models could help analyze systemic risk under stress scenarios.